Technological Tools for Knowledge Apprehension and Promotion in the Cultural and Heritage Tourism Sector: Systematic Literature Review - Jefferson Quiroz-Fabra; Alejandro Valencia-Arias; Wilmer Londoño-Celis; Vanessa García-Pineda (Human Behavior and Emerging Technologies)
One of the objectives sought within the teaching-learning processes is the apprehension of knowledge. In the cultural and heritage tourism sector, these processes are integrated with the help of the Information and Communications Technologies (ICT), such as immersive technologies, to develop new forms of interaction, improve the user experience, disseminate knowledge, and promote these destinations. Given the boom in technological development and its application in tourism, this study is based on analyzing through a systematic literature review the research progress that has been made in this area. The proposed methodology comprises a series of information search and characterization stages in which 54 studies are analyzed. The systematic analysis and breakdown stage highlights the use of gamification and e-Learning as key tools for the apprehension of knowledge in tourism environments, showing its versatility in developing digital tools for different contexts. The results allow proposing a research agenda based on three key components: e-Learning as an instrument of interactive education where technologies are articulated with pedagogical aspects, dynamic marketing, and its replicability in different tourism sectors, as well as the development of advergames and the development of gamification techniques and games from the technological field and its characteristics as an evaluative tool in the field of learning.